(untitled) (Research, Society and Development, 2021)
Adsorption is a surface phenomenon, in which the adsorbate is adhered to an adsorbent material and have been study for the removal of textile dyes, which have high toxicity to the aquatic environment. One of the dyes that stands out is methylene blue, which is organic, basic, aromatic, heterocyclic and molecular formula (C16H18ClN3S). In this study, we aim was to carry out a bibliography review in national and international scientific journals with articles published in the period from 2005 to 2019, of the adsorbent materials for the adsorption of the methylene blue dye. The materials reported are: mango seed powder, wheat husks, activated carbon obtained from rattan sawdust, activated carbon prepared from coconut shell, garlic shell, NaOH modified pummell shell, activated carbon (coconut shell and modified with NaOH), activated carbon (pea peel), HCl modified watermelon peel, potato peel, ZnCl2 activated cashew nut peel, mesoporous carbon obtained from fish scales, pineapple peel and bamboo. Our review indicate that the adsorbent materials found in the literature for methylene blue adsorption have high adsorption capacities. The adsorption capacities are high and depend on several parameters, which influence the adsorption (pH of the medium, mass and particle size of the adsorbent material, concentration of adsorbate (methylene blue), temperature and time of contact of the adsorbate with the adsorbent.